Bioerosion in the Miocene Reefs of the northwest Red Sea, Egypt. (25th November 2015) - Abdel‐Fattah, Zaki A.; Assal, Ehab M.
Abstract : Macroborings provide detailed information on the bioerosion, accretion and palaeoenvironment of both modern and fossil reefs. Dolomitized reefal carbonates in the Um Mahara Formation exhibit an outstanding example of spatially distributed, well‐preserved bioerosion structures in tropical to subtropical syn‐rift Miocene reefs. Ten ichnospecies belonging to five ichnogenera are identified; three belonging to the bivalve‐boring ichnogenus Gastrochaenolites, three attributed to the sponge‐boring ichnogenus Entobia, and four ichnospecies assigned to three worm‐boring ichnogenera Trypanites, Maeandropolydora and Caulostrepsis . The distribution of the reported borings is strongly linked to the palaeo‐reef zones. Two distinctive ichnological boring assemblages are recognized. The Gastrochaenolites ‐dominated assemblage reflects shallower‐marine conditions, under water depths of a few metres, mostly in back‐reef to patch‐reef zones of a back‐reef lagoon. The Entobia ‐dominated assemblage signifies relatively deeper marine conditions, mostly in reef core of the fringing Miocene reefs. These ichnological assemblages are attributed herein to the Entobia sub‐ichnofacies of the Trypanites ichnofacies. This ichnofacies indicates boring in hard carbonate substrates (such as corals, rhodoliths, carbonate cements and hardgrounds) during periods of non‐sedimentation or reduced sediment input.